2004
DOI: 10.1111/j.1365-2273.2004.00859.x
|View full text |Cite
|
Sign up to set email alerts
|

Molecular markers in dysplasia of the larynx: expression of cyclin-dependent kinase inhibitors p21, p27 and p53 tumour suppressor gene in predicting cancer risk

Abstract: Premalignant conditions affect the larynx. Dysplasia can progress in severity resulting in cancer depending on many clinical, pathological and molecular factors. The purpose of this study was to examine the expression of the p21 and p27 cyclin-dependent kinase inhibitors and p53 tumour suppressor gene in dysplasia of the larynx. A total of 114 cases of untreated dysplasia were selected from the archives of the University of Newcastle. p21, p27 and p53 immunohistochemistry was performed and the cases followed u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0
2

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(36 citation statements)
references
References 19 publications
0
34
0
2
Order By: Relevance
“…In a study of 114 cases of untreated dysplasia of the larynx, Jeannon et al [21] found that expression of p53 was not associated with cancer progression. In their study, Hirai et al [14] revealed that p53 immunostaining was observed in 6 out of 20 cases of hyperplasia, 3 out of 19 cases of dysplasia and 7 out of 17 cases of carcinoma, no significant association was found between p53 and the histopathological findings.…”
Section: Discussionmentioning
confidence: 99%
“…In a study of 114 cases of untreated dysplasia of the larynx, Jeannon et al [21] found that expression of p53 was not associated with cancer progression. In their study, Hirai et al [14] revealed that p53 immunostaining was observed in 6 out of 20 cases of hyperplasia, 3 out of 19 cases of dysplasia and 7 out of 17 cases of carcinoma, no significant association was found between p53 and the histopathological findings.…”
Section: Discussionmentioning
confidence: 99%
“…More precisely, p16 (p16INK4A) was analyzed in a case-control study where reduction of p16 expression tended to be more frequent in cases than in controls [25]. p21 and p27 expression was assessed in a retrospective study, but none of these proteins were associated with malignant progression [17].…”
Section: Cell Cycle Regulatorsmentioning
confidence: 99%
“…Most studies investigate the inactivation of the TP53 gene by immunohistochemical analysis of p53 protein levels, in light on the fact that the half-life of the wild-type protein is too short to permit its detection, while the mutant protein is stable. The p53 protein expression as a biomarker of laryngeal cancer risk has been assessed in four retrospective studies [13,[15][16][17] and three case-control studies [23][24][25]. These studies used different scoring systems for p53 staining, which prevents a direct comparison of the results.…”
Section: Cell Cycle Regulatorsmentioning
confidence: 99%
“…Several studies of OIN generally agree that the severity of epithelial abnormality reflects the degree of risk of SCC development (Jeannon et al 2004). No marker or group of markers has so far been identified as a reliable predictor of malignant progression of SILs.…”
Section: Additional Markers Of Malignant Alterations Of Oral Intraepimentioning
confidence: 99%
“…The grades do not offer clear therapeutic guidelines to clinicians for appropriate management. For CIS at least, the WHO grading system diagnoses CIS showing maturation and differentiation as lower risk lesions, and these lesions account for a large proportion of cases in the oral mucosa (Hellquist et al 1982;Gillis et al 1983;Yoo et al 2004;Kleist&Poetsh 2004;Jeannon et al 2004;Chi et al 2004).…”
Section: Who Classificationmentioning
confidence: 99%